Analisis Nilai Kehidupan Dalam Cerpen “Gubrak” Karya Seno Gumira Ajidarma Dengan Pendekatan Semiotika - Asni Asmawati; Isma Khoiriyah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
Literary works are literary results, creations in the form of poems, prose, and plays (drama). Literary works are born as embodiments or depictions of life poured through the medium of writing. Therefore, it is closely related between literature and life. Through literature, the reader can express the meaning behind the work of the author. This research would examine a short story entitled "Gubrak!" by Seno Gumira Ajidarma. "Gubrak!" short story tells about a beauty that actually creates its own wounds. The purpose of this study was to describe the meaning of multiplication (perlexia) and the analysis of the five Barthes codes contained in the short story "Gubrak!" using Roland Barthes's theory of semiotics. The methods used in this study were qualitative descriptive methods as well as semiotic approaches with Roland Barthes' five-code semiotic theory consisting of hermeneutic codes, semic codes, symbolic codes, action codes, and referential codes. The result of this study was the discovery of 53 lexicons, each of which has a meaning, including 9 hermeneutic codes, 29 semic codes, 5 action codes, 3 referential codes, and 8 symbolic codes. Through this analysis, the meaning and message could be drawn that you have enough because anything excessive is not good. This research would analyze the hidden signs in each word or sentence in the short story. Barthes semiotics was used to find out the meaning contained in the short story so it is interesting to study using the Barthes five-code approach.